Pengembangan Instrumen Smart Parenting pada Anak Usia 0-3 Tahun - Made Rismawan; Ni Kadek Sriasih; Ida Bagus Ardhi Putra; Ni Putu Riza Kurnia Indriana (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Disorders of child development have the potential to become long-term health problems. This can be prevented by carrying out child development assessments that are carried out independently by parents. However, the instruments for assessing growth and development are still conventional in the form of paper base, can only be used by health workers, and cannot be accessed by families so it would be less effective in early detection of disorders of child development. This study aimed to evaluate instruments for assessing the growth and development of children aged 0-3 years. The research design is descriptive with a Research and Development approach. This research was conducted in four villages in the Working Area of Puskesmas III Kintamani in August-September 2022. Data was collected by evaluating 284 growth and development assessment forms and Focus Group Discussions attended by seven mothers with children aged 0-3 years. The results showed that six elements in the growth and development assessment form were not found, namely the elements of the instrument usage guide, parental knowledge, assessment parameters, early detection of growth and development scores, management algorithms according to scores and health education about child growth and development. Meanwhile, there were 10 elements found but not appropriate in the child development assessment form. Participants in the Focus Group Discussion have provided input, so it is necessary to continue preparing strategic issues and consulting experts.